Paskah Kristiani Menggenapi Kovenan Mesianik Dalam Kejadian 3:15 [The Christian Passover Fulfills the Messianic Covenant in Genesis 3:15] - Setiawan, Tjutjun; Rondonuwu, Fery; Suaji, Sri Darajat; Simon, Simon (Diligentia: Journal of Theology and Christian Education, 2023)
Passover celebrations are always repeated every year for Christians, although not as festive as Christmas. Christian Passover events are a series of events from the death of Jesus Christ on the cross and His resurrection on the third day. There have been many attempts to reduce the events of the cross and deny the crucified figure of Jesus Christ. This research tries to explore and examine the meaning of Easter in Christianity and how it relates to the Messianic Covenant in Genesis 3:15. The method used is qualitative with a literature review approach, examining the red threads of the Old and New Testaments regarding Passover, where in the conclusion there is a relationship between Genesis 3:15 concerning the Messianic covenant as a type and its antitype or fulfilment is in the event of the cross, and this is a work God's salvation in overcoming human sin, on the one hand God's justice is satisfied by punishing sin on the cross, and on the other hand it shows God's love for humans. Thus, as people who believe in Jesus Christ, they must understand the meaning of this Passover in their daily lives, and moreover, theological high school students and church pastors must understand that and educate the congregation to maintain the spirit of Passover. BAHASA INDONESIA ABSTRACT: Perayaan Paskah selalu berulang setiap tahun bagi umat Kristiani, meskipun tidak semeriah Natal. Peristiwa Paskah adalah suatu rangkaian peristiwa dari kematian Yesus Kristus di kayu salib dan kebangkitan-Nya pada hari yang ketiga. Banyak upaya untuk mereduksi peristiwa salib dan menafikan sosok Yesus Kristus yang tersalib. Penelitian ini mencoba menggali dan mengkaji makna paskah dalam kekristenan dan apa hubungannya dengan kovenan Mesianik dalam Kejadian 3:15. Metode yang dipergunakan adalah kualitatif dengan pendekatan kajian Pustaka, menelisik benang merah Perjanjian Lama dan Perjanjian Baru tentang Paskah, di mana dalam simpulan terdapat hubungan antara Kejadian 3:15 tentang kovenan Mesianik sebagai tipe dan antitipenya atau penggenapannya ada pada peristiwa salib, dan ini merupakan karya keselamatan Allah dalam mengatasi dosa manusia, di satu sisi keadilan Allah terpuaskan dengan menghukum dosa di salib, dan di sisi lainnya menunjukkan kasih Allah pada manusia. Dengan demikian sebagai umat yang percaya kepada Yesus Kristus harus memahami makna Paskah ini dalam kehidupan sehari-hari dan terlebih bagi mahasiswa Sekolah Tinggi Teologi dan para gembala gereja harus memahami itu dan mengedukasi jemaat untuk tetap menjaga semangat Paskah.